Biodiversity value of tree vegetation in Rainbow Forest Biosite, Ijen Geopark, East Java, Indonesia - HARI SULISTIYOWATI; ELA APRILIYANTI HASANAH; ARIF MOHAMMAD SIDDIQ; TRI RATNASARI; NILASARI DEWI; AGUNG SIH KURNIANTO (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Sulistiyowati H, Hasanah EA, Siddiq AM, Ratnasari T, Dewi N, Kurnianto AS. 2024. Biodiversity value of tree vegetation in Rainbow Forest Biosite, Ijen Geopark, East Java, Indonesia. Biodiversitas 25: 2670-2678. Biodiversity value representing the monetary estimation of the ecological value (ecoval) of species composing a forest is often applied for ecosystem change assessment. Tree community in Rainbow Forest Biosite (RFB) or Biosite Hutan Pelangi, Ijen Geopark, East Java, Indonesia was planted in 1937 and has experienced significant regrowth and changes over time by replacing one another until a mature forest becomes established. Yet, no empirical work has been done to assess the biodiversity value in RFB. Therefore, this study aims to provide a comprehensive estimation of the ecological value of tree vegetation in the RFB at Ijen Geopark. As many as 100 plots with size of 10×10 m each were established to acquire structural data of tree vegetation. Semi-destructive method was used to collect functional data on tree carbon. The result shows that RFB comprises 21 families, 34 genera, and 43 species. This forest has high diversity with dominant tree species are Trevesia sundaica Miq. and Dendrocnide stimulans (L.fil.) Chew due to the large number of individual and area coverage. Tree vegetation in RFB has a total basal area of 330 m2/ha and a total volume of 4,171.01 m3/ha, equivalent to an ecoval 182,439,286,595 IDR/ha in monetary terms. Three species including Agathis dammara (Lamb.) Rich. & A.Rich. and Cedrela odorata L., have unique existence, while others are quite unique (88.37%). Tree growth in RFB sequesters approximately 9,773.30 Mg CO2eq/ha while storing 873.17 Mg C/ha and producing 7,105.19 Mg O2eq/ha, equivalent to an ecoval of 11,401,417,827 IDR/ha. In total, the combined structural and functional biodiversity value of the explored vegetation is estimated to be 193,840,704,423 IDR/ha. By assigning this biodiversity value to RFB, authorities should focus on designing and implementing policies to maintain the existing tree species composition naturally and prevent deforestation.